2016
DOI: 10.1111/cbdd.12863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel dasatinib analogues as potent DDR1 and DDR2 kinase inhibitors

Abstract: Novel dasatinib analogues as DDR1 and DDR2 inhibitors were designed and synthesized. The synthesized compounds were screened for DDR1 and DDR2 kinase inhibitory and cancer cell proliferation inhibitory activities. Some of the compounds showed the potent inhibitory activities against both DDR1 and DDR2, as well as anticancer activity in low nanomolar range against K562 cell line; especially, compound 3j demonstrated significantly better inhibitory potency than the parental dasatinib against both DDRs and also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Screening of a focused library of approximately 2000 compounds originally designed as Bcr-Abl inhibitors followed by structural optimization led to the identification of a new class of DDR1 inhibitors (23). 19 Fragment-based screening of a library of 1500 compounds in combination with structural biology and computational modeling allowed identification of another class of DDR1/2 ligands [structure 24 in Supplemental Figure 5 20 ]. Lastly, virtual screening of a commercially available library of approximately 230 000 compounds was used to identify new DDR1 inhibitors [see Supplemental Figure 5 for structures 18− 25 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of a focused library of approximately 2000 compounds originally designed as Bcr-Abl inhibitors followed by structural optimization led to the identification of a new class of DDR1 inhibitors (23). 19 Fragment-based screening of a library of 1500 compounds in combination with structural biology and computational modeling allowed identification of another class of DDR1/2 ligands [structure 24 in Supplemental Figure 5 20 ]. Lastly, virtual screening of a commercially available library of approximately 230 000 compounds was used to identify new DDR1 inhibitors [see Supplemental Figure 5 for structures 18− 25 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, efforts to identify an appropriate chemical probe to modulate the activity of DDR1 in an in vivo model have been unsuccessful, largely because investigated molecules lack selectivity across the kinome. Although an unselective profile is tolerable in a preclinical study, it is an unacceptable safety risk in a longer clinical study for a chronic treatment indication such as CKD. The challenge in creating the required selective ATP-competitive DDR1 inhibitor resides in the high homology existing in the kinase domains bound by such molecules .…”
mentioning
confidence: 99%
“…In another study, Liu et al, synthesized novel dasatinib derivatives with potent DDR1 and DDR2 inhibitory activities [ 147 ]. One of the synthesized compounds, compound 39 ( Figure 16 A), compared with the parental dasatinib ( 1 ), demonstrated a considerably superior inhibitory potency over both DDRs and K562 cell lines (IC 50 values of 2.26 ± 0.46 nM for DDR1, 7.04 ± 2.90 nM for DDR2, and 0.125 ± 0.017 nM for K562 cell line).…”
Section: Small Molecule Ddr Kinase Inhibitorsmentioning
confidence: 99%
“…They showed that the DDR1 inhibitor 10 (DDR1-IN-1; DDR1 enzyme IC 50 105 nM) inhibited melanoma cell proliferation in both in vitro and ex vivo assays of hereditary Alport syndrome, tubular obstructive nephropathy and nephrotoxic serum glomerulonephritis, and was effective in animal melanoma xenograft models. Liu et al [ 27 ] reported the design and evaluation of novel dasatinib analogues as DDR1 and DDR2 inhibitors. Compound 19 was superior to dasatinib ( 7 ) against both DDRs, and demonstrated potent inhibitory activity against K562 cell lines (IC 50 values of 2.26 nM for DDR1, 7.04 nM for DDR2 and 0.125 nM for the K562 cell line).…”
Section: Selective Ddr1 Inhibitorsmentioning
confidence: 99%